Non-communicable disease competencies in undergraduate medical (MBBS) curriculum of Patan Academy of Health Sciences, Nepal - Shrestha, Shrijana; Shrestha, Ashis; Devbhandari, Ranjan Prasad; Acharya, Samita; Paudyal, Buddhi Prasad (Journal of Patan Academy of Health Sciences, 2023)
In the absence of equitable and well-established health care delivery system, the populations of lower middle income countries are more vulnerable to the impact of the non-communicable diseases (NCDs). However, adequate focus on teaching the NCD related competencies in the curriculum of medical professionals is missing in many of these countries. The South-East Asia Regional (SEAR) NCD Network took an initiative to evaluate the NCD competencies in the pre -service curriculum of the health care providers. As part of this initiative Patan Academy of Health Sciences (PAHS), School of Medicine (SOM) conducted a competency matching exercise for the NCD related competencies in its undergraduate medical (MBBS) curriculum using the tools and format developed by SEAR NCD Network Partners. It was found that 46 out of 55 listed competencies were either fully or partially covered while 10 of the competencies were not addressed in the PAHS MBBS curriculum. Following this exercise, the working group at PAHS School of Medicine has come up with an action plan, has identified a few NCD related competencies to be certified along with the tools and timing of certification Competency in NCD management ensures that future physicians have the necessary skills and knowledge to provide appropriate treatment and care for patients with NCDs through early detection and effective patient education which can reduce the burden of NCDs and the costs associated.